Optimization of secondary flow path clearance in centrifugal blood pump: a combined numerical and experimental study - Zhu, Chenying; Ye, Ping; Chang, Zhaohua (Frontiers in Physiology, 2025)
IntroductionBlood pumps as mechanical circulatory support (MCS) devices are widely used for patients with ventricular heart failure, and improving blood compatibility remains a key focus for researchers.MethodsThe effects of secondary flow path clearance on the performance and hemocompatibility of a centrifugal blood pump are investigated in this study. A blood pump of the specific design was developed for modeling and computer simulation, and 25 models were generated by varying its internal and outer clearance between 600 and 1,000 μm. This study systematically investigates the hydrodynamic and hemodynamic performance of designed blood pumps through integrated computational fluid dynamics simulations and in vitro hydraulic experiments.ResultsKey findings reveal a strong agreement between numerical predictions and experimental data, showing a maximum pressure deviation of 9% for the baseline pump configuration. Furthermore, the effect of the change in clearance on the head and efficiency is less than ±3%. The change in the secondary flow path significantly impacts hemolysis performance.DiscussionAn optimal clearance combination exists in the designed model, and for a specific flow field structure, asymmetric clearance may be an effective means to balance leakage control and turbulence suppression. Although the findings are specific to the pumps examined in this study, they provide valuable insights into the optimal design of blood pumps.